2001
DOI: 10.1074/jbc.m104838200
|View full text |Cite
|
Sign up to set email alerts
|

βIII Spectrin Binds to the Arp1 Subunit of Dynactin

Abstract: Cytoplasmic dynein is an intracellular motor responsible for endoplasmic reticulum-to-Golgi vesicle trafficking and retrograde axonal transport. The accessory protein dynactin has been proposed to mediate the association of dynein with vesicular cargo. Dynactin contains a 37-nm filament made up of the actin-related protein, Arp1, which may interact with a vesicle-associated spectrin network. Here, we demonstrate that Arp1 binds directly to the Golgi-associated ␤III spectrin isoform. We identify two Arp1-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
160
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 35 publications
3
160
1
1
Order By: Relevance
“…On the other hand, it is well known that dynactin interacts with and activates cytoplasmic dynein (33). Further, it has been shown that dynactin may recruit dynein to cargo in membrane vesicles directly (34) or indirectly via cytoskeletal proteins such as spectrin (35)(36)(37). Hence, in our future work, we will test the prediction that dynactin and spectrin may mediate the interaction between ClC-2 and dynein.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is well known that dynactin interacts with and activates cytoplasmic dynein (33). Further, it has been shown that dynactin may recruit dynein to cargo in membrane vesicles directly (34) or indirectly via cytoskeletal proteins such as spectrin (35)(36)(37). Hence, in our future work, we will test the prediction that dynactin and spectrin may mediate the interaction between ClC-2 and dynein.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Golgi protein Bicaudal-D binds to both dynein and the p50/dynamitin subunit of dynactin to regulate COP1-independent Golgi-ER transport [6][7][8]. Another Golgi-associated protein, βIII spectrin, binds to the Arp1 subunit of dynactin and is believed to link the motor to membranous cargo [9]. The huntingtin protein facilitates vesicular transport of brain-derived neurotrophic factor via the interaction between huntingtin-associated protein-1 and p150 Glued [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, dynactin has been found to be essential for nearly every cellular function of cytoplasmic dynein, such as cargo loading, dynein localization and maintaining processivity 5,8 . For example, Arp1 filament of dynactin binds to bIII spectrin, a filamentous protein that is found on the cytosolic surface of the Golgi and other cellular membranes 9 . Dynactin p150 Glued is also an important component for connection of a dynactin complex with a dynein motor.…”
mentioning
confidence: 99%